Major and Minor Head Losses Analysis on The Piping System in Pondok Pesantren Tahfizhul Qur'an Ibnu Abbas Tarakan - Sudirman (BEST, 2021)
The head loss analysis in this study is focused on the existing piping system at the Ibnu Abbas Tarakan Tahfizhul Qur'an Islamic Boarding School, so that it is known that the flow losses that occur are both major losses and minor losses. The stages taken are; literature review by reviewing several previous studies then continued with data collection on the piping system in Ibnu Abbas Tarakan Islamic Boarding School. The discussion of head losses in the piping system is divided into four parts according to the existing branching of the pipe installation when the water comes out of the pump. Head losses in each section, namely; the first section (A) 0.21 m, the second section (B) 0.47 m, the third section (C) 0.3 m. Whereas in the fourth section, the existing pipe installation is not supplied by water when the water flow from the pump is distributed simultaneously in the four existing pipe branches. The pump is unable to serve the existing pipe installation, if it is flowed simultaneously.